Efeitos agudos do exercício resistido sobre marcadores da resposta inflamatória e imune - Pereira, Guilherme Borges (2012)
The purpose of the present study was to examine the acute effects of resistance training (RT) on CD4+ and CD8+ T lymphocytes apoptosis (annexin V+) and migration (CX3CR1). Twelve subjects performed two RT sessions (3 sets of 9 exercises) with 1 min (Hyper-1) and 3 min (Hyper-3) of rest-interval length between sets and exercises. CD4+ and CD8+ cells count displayed no change following Hyper-1 and Hyper-3 (p > 0.05). There was an increase in the percentage of CD4+ positive for annexin V+ and CX3CR1+ immediately after and 24 h post Hyper-1 (p < 0.05). Percentage of CD4+ positive for annexin V+ increased 2 and 24 h post Hyper- 3, and decreased after CX3CR1+ for the same time-points (p < 0.05). There was an increase in CD8+ positive for annexin V+ and CX3CR1+ immediately after, 2 and 24 h post Hyper-1 and Hyper-3 (p < 0.05), while no differences were found between Hyper-1 and Hyper-3 (p > 0.05). Acute RT increase the apoptosis and migration of CD4+ and CD8+ lymphocytes even 24 h after exercise, with minimal effects of restinterval length.